2015
DOI: 10.1016/j.jbi.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Mapping patient path in the Pediatric Emergency Department: A workflow model driven approach

Abstract: The workflow models of the patient journey in a Pediatric Emergency Department (PED) seems to be an effective approach to develop an accurate and complete representation of the PED processes. This model can drive the collection of comprehensive quantitative and qualitative service delivery and patient treatment data as an evidence base for the PED service planning. Our objective in this study is to identify crowded situation indicators and bottlenecks that contribute to over-crowding. The greatest source of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…A growing trend is the graphical representation of work processes and/or patient journeys. Ajmi et al [15] analyzed the patient path in a pediatric emergency department through a model-driven approach.…”
Section: Discussionmentioning
confidence: 99%
“…A growing trend is the graphical representation of work processes and/or patient journeys. Ajmi et al [15] analyzed the patient path in a pediatric emergency department through a model-driven approach.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of papers are discussed briefly and their relevant categories are indicated in Table 1 Ajmi et al, [3] used Business Process Modelling Notation (BPMN) to model the workflows of the patient journey in a Paediatric Emergency Department. The aim was to identify bottlenecks and crowded situation indicators, with noting that delay occurs in the waiting time from the health care request.…”
Section: Exploration Of a Sample Of Papersmentioning
confidence: 99%
“…It is important to note that only 12 papers [3,22,52,60,73,93,96,119,120,124,143,170] state that their research/product was implemented/informed policythis is only 6.9% of the papers surveyed. Previous reviews have found similar results in regards to implementation (e.g.…”
Section: Obtaining the Pathwaymentioning
confidence: 99%
See 2 more Smart Citations